(Z)-1,4-Bis(2-chlorophenyl)-2-(methylsulfanyl)but-2-ene-1,4-dione - A. J. Ravi; A. C. Vinayaka; K. R. Roopashree; M. P. Sadashiva; H. C. Devarajegowda. (IUCrData, 2017)
In the title compound, C17H12Cl2O2S, the benzene rings are inclined to one another by 84.59 (16)°. The enaminone group is present in a synclinal conformation with respect to the chlorobenzene moiety. The configuration of the C=C bond is Z. There is a short intramolecular C—H...O contact present forming an S(6) ring motif. In the crystal, molecules are linked by C—H...O hydrogen bonds, forming layers lying parallel to the (10-1) plane.